1990
DOI: 10.1155/1990/261504
|View full text |Cite
|
Sign up to set email alerts
|

The Neurology of Proverbs

Abstract: Although proverb tests are commonly used in the mental status examination surprisingly little is known about either normal comprehension or the interpretation of proverbial expressions. Current proverbs tests have conceptual and linguistic shortcomings, and few studies have been done to investigate the specific effects of neurological and psychiatric disorders on the interpretation of proverbs. Although frontal lobes have traditionally been impugned in patients who are “concrete”, recent studies targeting defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 45 publications
(58 reference statements)
0
23
0
2
Order By: Relevance
“…Some recent research has indicated that RH processes may be more important for understanding very unfamiliar and more complex metaphors (Bottini et al, 2007;Mashal et al, 2005;Schmidt, DeBuse, & Seger, 2007). It is also possible that greater RH involvement would occur with pictorial stimuli (Rinaldi, Marangolo, & Baldassarri, 2004;Winner & Gardner, 1977), with other Wgurative forms (Coulson & Williams, 2005;Kempler et al, 1999;Van Lancker, 1990), and in more naturalistic discourse situations involving higher-level inferences and pragmatic processing (Brownell, Gardner, Prather, & Martino, 1995;Sabbagh, 1999). Regardless of these limitations, the main strength of the present investigation involved the systematic study of normal participants with a large, carefully designed, and normed set of stimuli using the same basic paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent research has indicated that RH processes may be more important for understanding very unfamiliar and more complex metaphors (Bottini et al, 2007;Mashal et al, 2005;Schmidt, DeBuse, & Seger, 2007). It is also possible that greater RH involvement would occur with pictorial stimuli (Rinaldi, Marangolo, & Baldassarri, 2004;Winner & Gardner, 1977), with other Wgurative forms (Coulson & Williams, 2005;Kempler et al, 1999;Van Lancker, 1990), and in more naturalistic discourse situations involving higher-level inferences and pragmatic processing (Brownell, Gardner, Prather, & Martino, 1995;Sabbagh, 1999). Regardless of these limitations, the main strength of the present investigation involved the systematic study of normal participants with a large, carefully designed, and normed set of stimuli using the same basic paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Engages abstract verbal reasoning (Lezak, 1995) and higher order cognitive processes of figurative language comprehension (Van Lancker, 1990). Students read beginnings of proverbs to see if participants knew the ending.…”
Section: Proverb Completion and Interpretationmentioning
confidence: 99%
“…Given the sensitivity of a PI task to declines in abstract verbal reasoning (Van Lancker, 1990) and figurative language processing, we elected to use a proverb interpretation task as one of our discourse outcome measures. Chapman et al (1997) compared persons with fluent aphasia, persons with AD and healthy elders on their ability to interpret familiar and unfamiliar proverbs.…”
Section: Proverb Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Less frequently examined in communication science are formulaic or familiar, nonliteral expressions (FNEs), variously labeled as slang, idioms, speech formulas, sayings, pause fillers, conventional expressions, automatic or overlearned speech, expletives, cliches, maxims, slogans, proverbs, and so on. Studies of brain-damaged subjects suggest that novel and formulaic language are processed by different neurological structures (Van Lancker, 1990 Van Lancker & Kempler, 1987). People with aphasia are sometimes better able to produce overlearned than novel expressions (Jackson, 1874;Van Lancker, 1988;Code, 1982;Blanken et al, 1990), possibly attributable to right hemisphere (Graves & Landis, 1985).…”
mentioning
confidence: 99%